IMPLEMENTATION OF INNOVATIONS AS THE BASIS FOR IMPROVING TAX AUDIT - Sembiyeva L. M.; Serikova M. A.; Zhagiparova A. O.; Korzeb Zbigniew (Scientific Journal of Pedagogy and Economics, 2019)
This scientific article analyzes research and identifies the main directions to the definition of innovation in the sphere of state tax audit and management. The research of CIS scientists in the field of innovations in the public sector is described and the directions of modernization of tax regulation according to the strategic documents of the Republic of Kazakhstan are given. The dependence of tax revenue collection on the level of innovation activity of Kazakhstan, OECD countries and neighboring countries is considered.